(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This study aims to determine the degree of professional stress among primary school teachers in the municipality of Ahmed Rachedi, Mila Province. The study found that the level of professional stress among primary school teachers in the municipality of Ahmed Rachedi is average, and that there is no correlation between the level of professional stress and the variables of gender and seniority.